Fish can use hydrostatic pressure to determine their absolute depth - Davis, V; Holbrook, R; Burt De Perera, T (Springer Nature, 2021)
Hydrostatic pressure is a global cue that varies linearly with depth which could provide crucial spatial information for fish navigating vertically; however, whether fish can determine their depth using hydrostatic pressure has remained unknown. Here we show that Mexican tetras (Astyanax mexicanus) can learn the depth of a food site and consistently return to it with high fidelity using only hydrostatic pressure as a cue. Further, fish shifted their search location vertically as predicted if using pressure alone to signal depth. This study uncovers new sensory information available to fish which allows them to resolve their absolute depth on a fine scale.